Bibliometric Computational Mapping Analysis of Publications on Zirconium Nanoparticles - Raden Melvin Fauzan Idat; Asep Bayu Dani Nandiyanto (JUMANTARA: Jurnal Manajemen dan Teknologi Rekayasa, 2023)
This study examines the development of research on Zirconium nanoparticles through a bibliometric approach with computational mapping analysis using VOSviewer. Journal article data was obtained from the Google Scholar database using the Publish or Perish application. The keywords used to search related journals are zirconium, nanoparticles, chemistry. There were 999 journal articles related to keywords. The range of journal articles searched from the Google Scholar database is the last 10 years (2012 – 2022). The results show that research zirconium nanoparticles can be separated into 2 terms: nanoparticle and zirconium. The term zirconium which included in cluster 1 with 271 links total, 1970 total link strength, and 343 occurrences, and the second term is nanoparticles which belongs to cluster 2 with a total of 270 links, a total link strength of 2556, and occurrences of 445. The results of the analysis of research developments in the last 11 years show a slight fluctuation. In 2012 – 2013 there was an increase in the number of studies from 34 to 62 (28 studies). It decreased from 2016-2017. This decline can be seen from the number of publications in 2016 (94 publications) to 2017 (86 publications). The development of zirconium nanoparticles research increased in the last 5 years, before a drastic decline in 2022. The results of the study indicate that the opportunity for research on zirconium nanoparticle still has a high enough chance and is linked to other terms.